Analisis Faktor-faktor Store Atmosphere yang Mempengaruhi Keputusan PEmbeli Konsumen pada SUpermarket dan Department Store Kaisar di Pontianak - Heng, Lie (MABIS, 2011)
This research was conducted to know the variables of store atmosphere which influence the purchasing decision behaviour of Kaisar Supermarket and Department Store visitors. This research was based on primary data collected from questioners distributed to respondents who are active visitors of Kaisar Supermarket and Department Store. The form of the research was descriptive research and the research method was survey method. Data analysis technique used in this research was quantitative analysis technique using factor analysis method. From the research result, the factors which influence the purchasing decision behaviour of Kaisar Supermarket and Department Store consumers were grouped into Product Display and Decoration factor, Store Facility and Layout factor, Store Physical Condition factor, Parking and Security factor, Building Information and Guide factor, Comfortability and Interior factor, Payment System factor and People.